Application of Gaultheria essential oil attractant to increase abundance zigzag ladybird beetle (Cheilomenes sexmaculata) and other coccinellids - SISKA EFENDI; DADANG DADANG; I WAYAN WINASA; ALI NURMANSYAH (Society for Indonesian Biodiversity, 2025)
Abstract. Efendi S, Dadang, Winasa IW, Nurmansyah A. 2025. Application of Gaultheria essential oil attractant to increase abundance zigzag ladybird beetle (Cheilomenes sexmaculata) and other coccinellids. Biodiversitas 26: 2674-2683. Gaultheria essential Oil (GeO) has the potential to be used as an attractant for Cheilomenes sexmaculata because of its high Methyl Salicylate (MeSA) content. The research aimed to evaluate the effectiveness of GeO attractant against C. sexmaculata and its effect on other coccinellids. The tested GeO attractant doses were 0.25 mL, 0.5 mL, 1 mL, and 2 mL/dispenser. The data was analyzed with the Kruskal-Wallis non-parametric median test, with a Mann-Whitney post-test corrected Holm test. The analysis uses the ggstatsplot package version 0.13.0 in R Studio software version 4.4.2. The causal relationship between attractants, abundance, coccinellid richness, and chili (Capsicum annuum) yield was analyzed using a Structural Equation Model (SEM). The results showed that GeO attractant affects the abundance of C. sexmaculata. The attractant GeO also accelerates the presence of C. sexmaculata in chili crops. In addition, GeO attractants also affect the abundance of other predatory coccinellids, namely Micraspis lineata, Harmonia decussata, Coelophora maculata, Coleophora inaequalis, Scymnus sp., Curinus coeruleus, Coccinella transversalis, and Cryptolaemus montrouzieri. The application of GeO attractants, abundance of C. Sexmaculata and Aphis gossypii are directly and significantly related to chili yield. GeO attractant can be a new component of Integrated Pest Management (IPM) to control A. gossypii in chili cultivation.